PRECONDITIONS AND REASONS FOR CHRISTIANITY TO BECOME A STATE RELIGION IN GREATER ARMENIA (GREAT HAYQ) IN THE SECOND HALF OF THE 3RD CENTURY - Sahakyan, Artsruni (Armenian Folia Anglistika, 2024)
The article highlights the domestic and global preconditions for Christianity to become a state religion in Hayq. The underlying reason and the social-political consequences have been specified, as well. As it follows, the religious situation in Greater Armenia did not allow the country to adopt a neutral position in the military and political race between the two super powers of the time, first because of its syncretic nature and later owing to Zoroastrian reforms. Hence, Greater Armenia faced a most decisive choice in favor of a new type of independence that was possible only through a religious neutrality – a step that Tiridates III realized thereby earning the title of the Great.
Keywords: Greater Armenia; Rome; Sassanid Persia; persecutions of Christians; Tiridates II; the Hripsimyans; Tiridates the Great; state religion